The myth of absence of lex fori towards the international arbitrator - Mimoso, Maria João (2017)
The national and foreign doctrines uphold the absence of lex fori for the international arbitrator since the origin of the international arbitration. Our goal is to emphasize the demand of electing a lex fori for the international arbitrator for as much there is a collection of issues concerning the intervention of the State Courts in the role of arbitration support. The lex fori, that is supposed to inquire, will assist the arbitrator in determining the applicable law to the dignity of the dispute, and will regulate, undoubtedly, the litigation issues of arbitration. Based on the predominately upheld position in the doctrine, we will provide evidence to the specific limitations of the most aimed efficacy of the arbitration decisions. We will demonstrate through the jurisprudential (arbitration) analysis the necessity of appealing to the State Courts, excelling their contribution for the arbitration success. For the international arbitrator, the focus of the arbitration in the quality of lex fori comes up as important. We will draft its potential regulation capacities while cohesive juridical system, mainly in the dissension subsystem, the principles and proceeding rules, without forgetting the legitimacy to apply other transnational system rules To deny the existence of a lex fori to the international arbitrator is a redundancy, for, beyond the arbitrator having a lordship, the arbitration court also has a lex fori.